Ocular findings as predictive and diagnostic factors of canine Erlichiosis - Trujillo Piso, Dunia Yisela (2019)
The aim of this study was to determine the possibility of predicting Ehrlichia canis infections based on canine eye lesions without apparent systemic clinical signs suggestive of Erlichia infection. A total of 30 patient dogs taken to the Veterinary Clinic of the Cooperative University of Colombia (Ibagué) for ocular alterations were evaluated. A complete ophthalmic examination was performed. Those with uveitis or retinal hemorrhages were subjected to the SNAP test for Ehrlichia canis. The main reason for ophthalmic consultation of patients positive for E. canis was ocular secretion (33.3%), followed by red eye (30%) and loss of vision (20%). In the ophthalmic examination, the most frequent ocular alteration was low intraocular pressure (IOP) (93.3%) and conjunctival hyperemia (63.3%). Moreover, 46.7% had an increase in ocular secretion and 40% were positive to keratoconjunctivitis sicca (KCS) (Rose Bengal +). Retinal detachment and perivascular edema of retinal vessels was found in 26.7% of patients. In conclusion, the red eye, low IOP and KCS of qualitative type are presented as early findings of canine ehrlichiosis; therefore, these signs should be considered as suggestive of the disease in endemic regions.